2023
DOI: 10.3390/rs15040902
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Perspective Response of Vegetation to Drought on the Qinghai-Tibetan Plateau

Abstract: The Qinghai-Tibetan Plateau (QTP) is a global center of cold and dry, where the most extensive fragile alpine vegetation exists. Quantitative analysis of drought event characteristics and vegetation response to drought on the QTP is indispensable for understanding the increasing drought events in a warming climate which exacerbate adverse influence on extremely alpine ecosystems. Here, using the standardized precipitation evapotranspiration index (SPEI) and the normalized difference vegetation index (NDVI) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…There are significant temporal effects of drought on vegetation in grassland areas of the QTP during the growing season, which reach their peak in July and August. Compared to the east monsoon region, most of the western regions have higher-frequency and lowerintensity drought events [16]. The drought chain phenomenon commonly occurs in western regions of the QTP where precipitation observations are lacking.…”
Section: The Drought Chain Methods For Estimating Precipitation Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant temporal effects of drought on vegetation in grassland areas of the QTP during the growing season, which reach their peak in July and August. Compared to the east monsoon region, most of the western regions have higher-frequency and lowerintensity drought events [16]. The drought chain phenomenon commonly occurs in western regions of the QTP where precipitation observations are lacking.…”
Section: The Drought Chain Methods For Estimating Precipitation Accuracymentioning
confidence: 99%
“…As one of the most widespread and costly hydrological imbalance phenomena in the world [15], higher frequency and lower intensity of drought events occur in western QTP [16]. Reanalysis and remote sensing precipitation products-based drought indices were shown to be able to capture the occurrence and characteristics of drought events; however, they are influenced by various sources, the complex topography, and atmospheric processes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the NDVI and NPP of vegetation increased based on satellite data and numerical models [33,34]. Furthermore, the responses of vegetation to drought changes presented various instances of spatial heterogeneity in the TP, which varies with the different vegetation types in different regions [14,[35][36][37][38][39]. For instance, Wang et al [40] and Wang et al [41] found enhanced drought caused the vegetation degradation in the southern and western regions, while Fang and Zhang [42] observed a negative impact of drought on vegetation in the southeastern areas.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have carried out research on the response of vegetation to drought, which has revealed the significant impact of drought on vegetation productivity. In addition, the response of vegetation to drought is very complex, which is closely related to vegetation type [10,11], dry and wet environment and drought time scale [12].…”
Section: Introductionmentioning
confidence: 99%